Analyzing the costs of developing and operating an integrated health-system specialty pharmacy: The case of a centralized insurance navigation process for specialty clinic patients. (9th March 2021) - Rim, Matthew H; Thomas, Karen C; Barrus, Stephanie A; Ryther, Ashley M K; Clawson, Antoine; Ferrara, Francesca; Jackson, Christopher G
Abstract: Purpose: Direct and indirect costs related to the growth of specialty pharmacy services and the insurance navigation process for specialty clinic patients are discussed, and development and implementation of a pharmacy-driven and system-wide prior authorization (PA) processing center within a health system are described. Summary: Expensive specialty drugs require PA. Due to the concentration of specialists, health systems with multiple specialties experience higher PA burden and resulting care delays. Although clinic staff typically handle PA requests, health-system specialty pharmacies are well positioned to support patients, clinic staff, and physicians by assuming responsibility for the PA process entirely. University of Utah Health established its Pharmacy Ambulatory Clinical Care Center (PAC3) to centralize PA processing for selected specialty and primary care clinics within the health system. In fiscal year 2019, the PAC3 team (10 pharmacy technician and 1.5 pharmacist full-time equivalents) completed over 13, 000 PAs. The pharmacy labor cost increase was significant; however, the benefits gained from increased services, quality, and financial strength surpassed all costs associated with the implementation and maintenance of the pharmacy operation. Other tangible benefits included decreased delays in therapy initiation, increased patient satisfaction, increased clinic visits, and increased staff and provider satisfaction and engagement. Conclusion: Increased PA requests associated with specialty drugs have placed considerable stress and staff burden on specialty clinics within health systems. However, development and implementation of an efficient PA processing infrastructure within a health-system specialty pharmacy may reduce the burden, increase financial strength, and improve the patient experience.